Airbag-Induced Thumb Avulsion: Two Case Reports. (March 2015) - Stoel, Anne-Marie C. C.; Vanhaecke, Jeroen; Dezillie, Marleen; Oosterlinck, Dirk; Stockmans, Filip
Although airbags are designed to save lives and protect victims from serious injuries, airbag deployment can cause unwanted lesions. In this case report, two cases are presented of young women who sustained an important fracture dislocation of the first carpometacarpal joint (CMC I joint) caused by airbag deployment during a car collision.